Terrestrial Heteroptera (Hemiptera) from Moconá Provincial park (Misiones, Argentina) - Dellapé, Gimena (2015)
Moconá Provincial Park was created to protect the Paranaense forest including the Moconá Falls Natural National Monument. Knowledge of the insect fauna in the park is scarce and the Heteroptera have never been studied. In this work, 134 species from 17 families of Heteroptera collected in Moconá Provincial Park and surrounding areas included in the Yabotí Biosphere Reserve, are listed. The reduviids Arilus gallus (Stål, 1872), Repipta taurus (Fabricius, 1803), and Zelus nugax Stål, 1862; the tingids Leptodictya (Hanuala) paspalii Drake & Hambleton, 1934, and Leptopharsa vittipennis (Stål, 1873); the coreids Camptischium niger (Stål, 1870), Leptoglossus ingens (Mayr, 1865), Chariesterus cuspidatus Distant, 1892 and Cebrenis supina Brailovsky, 1995; the pentatomids Alveostethus pseudopolitus (Ruckes, 1957) and Dryptocephala integra Walker, 1867; and the blissid Xenoblissus lutzi Barber, 1954 are first records from Argentina.